Sex-related response to bivalirudin and unfractionated heparin in patients with acute myocardial infarction undergoing percutaneous coronary intervention: A subgroup analysis of the VALIDATE-SWEDEHEART trial. Issue 6 (September 2019) - Venetsanos, D; Sederholm Lawesson, S; Fröbert, O; Omerovic, E; Henareh, L; Robertsson, L; Linder, R; Götberg, M; James, S; Alfredsson, J; Erlinge, D; Swahn, E
Aims: Our aim was to study the impact of sex on anticoagulant treatment outcomes during percutaneous coronary intervention in acute myocardial infarction patients. Methods: This study was a prespecified analysis of the Bivalirudin versus Heparin in ST-Segment and Non ST-Segment Elevation Myocardial Infarction in Patients on Modern Antiplatelet Therapy in the Swedish Web System for Enhancement and Development of Evidence-based Care in Heart Disease Evaluated according to Recommended Therapies Registry Trial (VALIDATE-SWEDEHEART) trial, in which patients with myocardial infarction were randomised to bivalirudin or unfractionated heparin during percutaneous coronary intervention. The primary outcome was the composite of death, myocardial infarction or major bleeding at 180 days. Results: There was a lower risk of the primary outcome in women assigned to bivalirudin than to unfractionated heparin (13.6% vs 17.1%, hazard ratio 0.78, 95% confidence interval (0.60–1.00)) with no significant difference in men (11.8% vs 11.2%, hazard ratio 1.06 (0.89–1.26), p for interaction 0.05). The observed difference was primarily due to lower risk of major bleeding (Bleeding Academic Research Consortium definition 2, 3 or 5) associated with bivalirudin in women (8.9% vs 11.8%, hazard ratio 0.74 (0.54–1.01)) but not in men (8.5% vs 7.3%, hazard ratio 1.16 (0.94–1.43) in men, p for interaction 0.02). Conversely, no significant difference in the risk of Bleeding Academic Research Consortium 3 or 5 bleeding, associated with bivalirudin, was found in women 4.5% vs 5.4% (hazard ratio 0.84 (0.54–1.31)) or men 2.9% vs 2.1% (hazard ratio 1.36 (0.93–1.99)). Bleeding Academic Research Consortium 2 bleeding occurred significantly less often in women assigned to bivalirudin than to unfractionated heparin. The risk of death or myocardial infarction did not significantly differ between randomised treatments in men or women. Conclusion: In women, bivalirudin was associated with a lower risk of adverse outcomes, compared to unfractionated heparin, primarily due to a significant reduction in Bleeding Academic Research Consortium 2 bleeds.